2014
DOI: 10.1177/0148607114532135
|View full text |Cite
|
Sign up to set email alerts
|

Use of 3 Tools to Assess Nutrition Risk in the Intensive Care Unit

Abstract: Traditional screening and assessment tools did not uniformly identify patients as malnourished or at nutrition risk in the ICU and therefore may be inappropriate for use in this population. Inclusion of physical assessment, functional status, and severity of illness may be useful in predicting nutrition risk in the ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 13 publications
2
60
0
12
Order By: Relevance
“…Most of the critically ill patients admitted to the ICU show malnutrition criteria [20]. Critical illness is typically associated with a catabolic stress state, skeletal muscle weakness, and as consequence with complications such as increased infectious morbidity, multiple-organ dysfunction, difficult weaning, prolonged hospitalization, and increased mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the critically ill patients admitted to the ICU show malnutrition criteria [20]. Critical illness is typically associated with a catabolic stress state, skeletal muscle weakness, and as consequence with complications such as increased infectious morbidity, multiple-organ dysfunction, difficult weaning, prolonged hospitalization, and increased mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional status can be evaluated by using tools such as the Subjective Global Assessment [2223], the Mini Nutritional Assessment [24], and the Malnutrition Clinical Characteristics [25] tools. Previous research has validated these scoring systems, but these tools typically cannot be used in patients un-dergoing emergency operations.…”
Section: Discussionmentioning
confidence: 99%
“…However, for the patients in intensive care units, to use only SGA or even Nutrition Risk in Critically ill score could be inappropriate, as they would not uniformly identify patients as malnourished. Hence, it would be useful to include physical assessment and functional tests to better predict nutrition risk in these patients (43). A Spanish study found that almost 63.3% of patients admitted to hospital were malnourished as assessed by SGA, but in the same time, another score, Instant Nutritional Assessment was the best single score to identify patients with/or at risk of malnutrition (44).…”
Section: Discussionmentioning
confidence: 99%